Occupation and cancer of the larynx: a systematic review and meta-analysis - Bayer, Oliver; Cámara, R.; Zeissig, S. R.; Ressing, Meike; Dietz, Angelika; Locati, L. D.; Ramroth, Heribert; Singer, S. (European archives of oto-rhino-laryngology and head & neck, 2016)
The aim of the study was to explore the relationship between occupational exposure, defined by occupational categories and job title, and laryngeal cancer. A systematic review and meta-analysis of 21 tobacco and alcohol-adjusted case-control studies including data from 6,906 exposed cases and 10,816 exposed controls was performed to investigate the frequency of laryngeal cancer in different occupations. Job classifications were harmonized using the International Standard Classification of Occupations. Pooled odds ratios (OR [95 % confidence intervals (CI)]) were calculated for the different occupational groups. A significantly increased risk of laryngeal cancer was observed for the occupational category of ‘production-related workers, transport equipment operators, and laborers’ (OR=1.3 [1.2-1.4]); particularly at risk were occupations as: miners (OR=1.6 [1.2-2.1]), tailors (OR=1.7 [1.2-2.3]), blacksmith and toolmakers (OR=1.5 [1.2-1.7]), painters (OR=1.4 [1.1-1.9]), bricklayers and carpenters (OR=1.3 [1.2-1.5]), and transport equipment operators (OR=1.3 [1.2-1.5]). Individuals working as ‘professional, technical, and related workers’ (OR=0.7 [0.6- 0.8]), ‘administrative and managerial workers’ (OR=0.6 [0.4-0.7]), or ‘clerical and related workers’ (OR=0.8 [0.7-0.9]) had laryngeal cancer less frequently. Occupational exposure, defined by occupational categories and job title, is likely to be an independent risk factor for laryngeal cancer. Further research on specific occupations with increased risk of laryngeal cancer is warranted to explore the underlying mechanisms.
Published online: 14 October 2014
Gesehen am 04.05.2020